EFEK PARTIKEL KEAUSAN MATERIAL PROTESA SENDI TERHADAP JUMLAH SEL RADANG (MAKROFAG) - Suhartini Suhartini (Fakultas Kedokteran Gigi Universitas Jember, 2013)
Replacement of joints with joint prostheses is one of the treatments to restore the function of joints damage. Wear particles is considered to be one of the main factors responsible for aseptic loosening of joint prostheses. Wear particles were generated from the wear test by using pin on plate unidirectional motion machine and PBS as a lubricant. The velocity of running test is 116.5 mm/s and the force is 180 N. The sliding distance of running wear test are 15 km and 30 km. Wear particles were inserted into knee joint synovium capsule of Rattus norvegicus sp. In the control groups, knee joint synovial capsule were injected with PBS without wear particles. On seventh day, the animals were sacrified, the tissues were collected for histology examination and the number of macrophages were determined. Statistical analysis showed that on there were no significant differences (p>0.05) in the number of macrophages. It can be concluded that the wear particles from stainless steel 316 L with ion implantation and UHMWPE GUR 1120 on 15 km and 30 km of sliding distance could not affect the number of macrophages.